Analisis Kinerja Ekonomi Sub-Sektor Peternakan Dalam Pembangunan Daerah Nusa Tenggara Barat Periode 2008-2018 - Moh. Taqiuddin; Soekardono; Anwar Fachry; Maya Nachida (Journal of Classroom Action Research, 2023)
The deliverable indicators for the results of the livestock sub-sector in West Nusa Tenggara over the past ten years (2008-2018) are still limited to performance-based measures from a technical standpoint of livestock farming and social welfare. Meanwhile, its performance in forming regional economic structures has yet to be well explored and analyzed. This study aims to analyze the economic performance of the livestock sub-sector in the West Nusa Tenggara economic development for the 2008-2018 period and to project its role in the future as well as to enrich theoretical discussions related to regional macroeconomic issues from an analysis of the role livestock sub-sector in the structure of West Nusa Tenggara regional economy over the last ten years (2008-2018). The results of the LQ analysis showed that the livestock sub-sector was included as the base sector in the regional economy during the 2008-2018 period, referring to the LQ>1 value was 1.31 along with 2 (two) other sub-sectors: food crops (1.49; LQ>1) and fisheries (1.01; LQ>1). The net shift value (Dij) of the livestock sub-sector also showed positive results (+), indicating that the livestock sub-sector was classified as progressive during the 2008-2018 period. Therefore, measures to increase the added value of livestock sub-sector products must continue to be developed by initiating livestock product processing.